Effectiveness of acupuncture on urinary retention after radical hysterectomy for cervical cancer in China: a systematic review and meta-analysis - Guo, Yong; Pan, Haixia; Chen, Siyang; Tian, Minne; Huang, Yanmei; Zhou, Ying (Frontiers in Medicine, 2024)
Background Cervical cancer is one of the most common malignant tumors worldwide. Radical hysterectomy is the first choice for patients with early-stage cervical cancer. Studies have suggested that acupuncture may be a more effective therapy for the prevention and treatment of urinary retention after radical hysterectomy. Objective To systematically evaluate the clinical efficacy of acupuncture in the prevention and treatment of urinary retention after radical hysterectomy. Methods We searched the Cochrane library, Web of science, PubMed, Embase, Chinese Biomedical Literature Database, Wanfang database, Wipu database, China National Knowledge Infrastructure Database and ClinicalTrials.gov with the time from inception until December 2023, to collect randomized controlled studies on the clinical efficacy of acupuncture for prevention and treatment of urinary retention after radical hysterectomy. Literature meeting criteria was screened for data extraction. Quality evaluation was performed according to the Cochrane Handbook for Systematic Reviews of Interventions. And meta-analysis was performed using RevMan5.3 and stata14.0 software. Results 22 Randomized controlled trials with 1,563 patients, 854 in treatment group and 709 in control group, were included totally. Meta-analysis results showed that: the total effective rate in acupuncture group was higher than that in control group, with a statistically significant difference [relative risk (RR)] = 1.43, 95% confidence interval (CI 1.22, 1.68), p < 0.0001; the rate of urinary tract infection in acupuncture group was lower than that in control group, with a statistically significant difference [RR] = 0.23, 95% CI (0.07, 0.78), p < 0.05; the time of indwelling urinary catheter was reduced in acupuncture group compared with control group, with a statistically significant mean difference = −3.45, 95% CI (−4.30, −2.59), p < 0.00001; the incidence of urinary retention was lower in acupuncture group than in control group, and the difference was statistically significant [RR = 0.37, 95% CI (0.27, 0.50), p < 0.00001]; the residual urine volume was reduced in acupuncture group compared with control group, with a statistically significant mean difference = −50.73, 95% CI (−63.61, −7.85), p < 0.00001. Conclusion Acupuncture treatment based on conventional therapy can better prevent and improve urinary retention after radical hysterectomy for cervical cancer, could be a better option for them. Systematic review registration Registered by PROSPERO and the registration number is CRD42023452387.